2015
DOI: 10.1007/jhep08(2015)092
|View full text |Cite
|
Sign up to set email alerts
|

Implications of μ-τ flavored CP symmetry of leptons

Abstract: Abstract:We discuss gauge models incorporating µ-τ flavored CP symmetry (called CP µτ in the text) in combination with L µ − L τ invariance to understand neutrino mixings and discuss their phenomenological implications. We show that viable leptogenesis in this setting requires that the lightest right-handed neutrino mass must be between 10 9 -10 12 GeV and for effective two hierarchical right-handed neutrinos, leptogenesis takes place only in a narrower range of 5 × 10 10 -10 12 GeV. A multi-Higgs realization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 110 publications
(261 reference statements)
4
90
0
Order By: Relevance
“…This form for the neutrino mass matrix in the flavor basis (diagonal charged lepton masses) is known to predict maximal θ 23 = 45 • and δ = ±90 • at the same time that θ 13 = 0 is allowed [4][5][6]. Additionally, the Majorana phases are trivial and four discrete choices for the CP parities are possible [4][5][6]9]. These features lead to characteristic predictions for the neutrinoless double beta decay rate and leptogenesis [9].…”
Section: Jhep01(2017)068mentioning
confidence: 95%
See 2 more Smart Citations
“…This form for the neutrino mass matrix in the flavor basis (diagonal charged lepton masses) is known to predict maximal θ 23 = 45 • and δ = ±90 • at the same time that θ 13 = 0 is allowed [4][5][6]. Additionally, the Majorana phases are trivial and four discrete choices for the CP parities are possible [4][5][6]9]. These features lead to characteristic predictions for the neutrinoless double beta decay rate and leptogenesis [9].…”
Section: Jhep01(2017)068mentioning
confidence: 95%
“…These values for the neutrino parameters are still allowed by current global fits and in fact there are hints that δ ∼ −90 • [7,8]. The fixed values for the CP phases also lead to characteristic bands for the possible effective mass of neutrinoless double beta decay but still allows leptogenesis to occur if flavor effects are taken into account [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We work in the basis in which charged leptons are mass diagonal. We are motivated by a flavor-based model constructed by Mohapatra and Nishi [42], which could accommodate a diagonal charged lepton mass matrix as well as a CP-transformed µτ interchange symmetry. Now we can relate U to the P M N S mixing matrix U P M N S : …”
Section: Jhep06(2018)085mentioning
confidence: 99%
“…Ref. [42] concluded that for the mass regime M 1 < 10 9 GeV, a resonant leptogenesis is only possible if one considers breaking in CP µτ , since in this regime the muon and tauon washout parameters are of equal strength. In our proposal of CP µτ A also, this conclusion is true.…”
Section: Jhep06(2018)085mentioning
confidence: 99%